DETERMINANT OF AUDIT DELAY IN INDONESIA - Edtiyarsih, Denari Dhahana (JEA17: Jurnal Ekonomi Akuntansi, 2023)
This research is a study using the literature study method which raises five recent studies in 2022 which project audit tenure, firm age, auditor relations, audit opinion, public accounting firm reputation, profitability, solvency, internal audit and the covid-19 pandemic, and committee audit against audit delay. The purpose of this study is to analyze more comprehensively the results of the five studies that have been carried out supported by other sources to increase literacy such as other research journals and books related to the analysis of determinants of audit delay.